Social determinants and oral health among cement industry workers - R. E. Haura Azzahra; Rosa Amalia; Derajad Sulistyo Widhyharto; Dibyo Pramono; Bambang Priyono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Cement industry workers are exposed to significant oral health risks due to hazardous conditions, but the role of social determinants in this context is not well understood. Purpose: This study investigates the association between social determinants and oral health among factory and office workers in the cement industry. Methods: A cross-sectional study was conducted at PT. Semen Padang, West Sumatra, Indonesia. A stratified random sample of 83 workers was selected. Social determinants were assessed using World Health Organization (WHO) 2013 and Perceived Stress Scale (PSS-10) questionnaires, while oral health was evaluated using decayed, missing, and filled teeth index (DMF-T), community periodontal index (CPI), and inspection. Ten calibrated dentists conducted dental examinations. Multiple linear regression was used for data analysis. Results: Factory workers exhibited higher rates of dental caries (95.83%), periodontal disease (87.50%), abrasion (91.67%), and attrition (87.50%), compared to office workers. Social determinants significantly associated with dental caries in factory workers included age, sugar intake, tooth-brushing frequency, and last dental check-up (r2 = 0.573), while only sugar intake was associated with caries in office workers (r2 = 0.290). For periodontal disease determinants associated with age, psychosocial factors, and smoking (r2 = 0.558) were significant in factory workers, whereas, in office workers, age, sugar intake, tooth-brushing frequency, last dental check-up, and smoking were significantly associated (r2 = 0.870). Age was the only significant determinant of abrasion and attrition in both groups. Conclusion: Social determinants influence oral health among cement industry workers, especially factory workers, due to physiological and psychological changes caused by working conditions. However, office workers also face oral health challenges due to poor oral health behaviors.